Analysis of factors affecting the semen pathology i n male infertility - Dr. Hetal Kumari Kishor Bhai Tandel; Dr. Yogita Kumari Manilal Patel (Tropical Journal of Pathology and Microbiology, 2019)
Background: Abnormalities in the male are the sole cause of infertility in approximately 20% of infertile couple and important contributing factor in another 20-40% of couple with reproductive failure. Despite our ability to assess sperm quality through a semen analysis methodology harmonized across laboratories, the use of these parameters cannot precisely and accurately predict the fertility of a man presenting to a clinician.Objectives: to evaluate various factors for male infertility and correlate various factors which affect the semen quality.Methodology: It was a prospective observational study done over a period of two years. Semen was examined for physical appearance, viscosity, volume, pH, sperm motility, biochemical test fructose, sperm count and the morphology for sperm was done.Results: 84% patients were presented as primary infertility and 16 % presented as secondary infertility. 35% of patients had oligozoospermia, 42.5% patients had oligoazoospermia and 17% of patients had azoospermia. Only 35 out of 118 smoker had >50% motility while 25 had motility of <5%. Also teratozoospermia dominated in alcoholics [65(32.5%)]. 25 out of 60 obese patients had sperm motility < 5%. While 10 out of 70 overweight and 5 out of 70 normal weight patients had sperm motility <5%.Conclusion: Smoking and alcohol decrease fertility by decreasing sperm count, motility and also by changing the morphology of sperm. Obesity also directly contributes in the fertility of a person by altering the hormonal status of patients.